Treatment of uterine sarcomas at the Maribor University Clinical Centre between 1996 and 2011 : Zdravljenje materničnih sarkomov v Univerzitetnem kliničnem centru Maribor v obdobju 1996–2011 - Arko, Darja; Dovnik, Andraž; Takač, Iztok (Acta Medico-Biotechnica, 2021)
Purpose: Uterine sarcomas are rare malignant tumours with a worse prognosis than endometrial carcinomas. This retrospective study was performed to determine the clinical and histologic characteristics, treatment, and outcomes in uterine sarcoma patients treated at our hospital over a 16–year period.Methods: Twenty–two patients (median age, 60.5 years) with uterine sarcomas were treated at our facility between 1996 and 2011. Information was collected from hospital and follow–up records and from the Cancer Registry of Slovenia. All tumours were classified according to the new FIGO classification for uterine sarcomas.Results: The majority of the patients presented with postmenopausal bleeding. The most common histologic subtype was leiomyosarcoma (50%), followed by carcinosarcoma (40.9%), and endometrial stromal sarcoma (9.1%). All of the patients were initially treated surgically, 21 by laparotomy and 1 laparoscopically. Eight patients were treated with post–operative radiotherapy and 4 patients received post–operative chemotherapy. Disease progression was observed in 8 of 17 patients who had sufficient follow–up information for this analysis. The 5–year overall survival was 44%.Conclusion: The overall survival of patients treated for uterine sarcomas in our study was comparatively good. Due to the small number and heterogeneity of the patients, larger multi–centre trials are needed for a reliable analysis of factors influencing patient survival.
Keywords: uterine sarcoma; histologic characteristics; surgical treatment; adjuvant therapy; overall survival